CREATIVE BRAINSTORMING TECHNIQUES IN GROUP GUIDANCE - Niswa, Aula; Agustin, Amanda; Agusty, Chelvi; Salwa, Nisrina (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This study aims to describe the application of creative brainstorming techniques in group counseling services as a strategy to help students develop critical and creative thinking skills in problem solving. Group counseling is a process in which a group of individuals receives information, guidance, and support from a counselor to help them deal with various issues in their daily lives, including decision-making. Through group counseling, students are guided to recognize and develop their potential, plan their future according to their talents and interests, and improve their verbal and nonverbal communication skills. This study used a qualitative descriptive method with a literature review approach. Data were collected through a review of various relevant reference sources, including books, scientific journals, and other documents discussing brainstorming techniques in the context of group counseling services. The results showed that brainstorming is an effective method for exploring various ideas from group members without judgment or criticism of the ideas that emerge. This technique has basic rules that support the creation of an open and free atmosphere for expressing opinions. Its main objective is to generate many ideas from various perspectives. The steps in this technique include selecting a problem, communicating the rules, freely recording ideas, and evaluating ideas as a group. The application of brainstorming in group counseling encourages a relaxed yet productive discussion atmosphere, allowing students to think creatively and find solutions from diverse perspectives.